Pelaksanaan Penanaman Bibit Bakau Sebagai Program Tanggung Jawab Sosial Perusahaan Oleh ASSA Rent Surabaya - Amelia Diva Effendy (Jurnal Kabar Masyarakat, 2023)
Social and environmental problems that arise in society are one of the negative impacts of industrial activities. Poverty, ignorance, access to life and clean water, environmental pollution, infectious diseases continue to occur continuously due to industrial activities. Industrial waste that is continuously disposed of carelessly is a continuous problem that can cause environmental pollution. Through the implementation of the corporate social responsibility program, ASSA Rent Surabaya carried out mangrove seed planting activities. The research method used is descriptive analysis which is qualitative in nature. Data collection was carried out by observation, literature study, and interviews. This study uses the theory of Charles O. Jones by identifying three pillars of activity namely organization, interpretation, and application. The results showed that ASSA Rent Surabaya had carried out the activity of planting mangrove seedlings as a corporate social responsibility program very well.